Will Shopee’s Virtual Try-On Trigger Modern Cosmetic Purchase Decisions in West Kalimantan? - Wulan Ramadhani; Rianti Ardana Reswari; Aisyah (Business, Economics dan Entrepreneurship, 2025)
The cosmetics industry in Indonesia is growing quickly as online shopping becomes more popular. However, consumers often have trouble figuring out if a cosmetic product is right for them just from pictures or descriptions on e-commerce platforms. This makes them hesitant to buy. In order to solve this problem, Shopee has introduced Augmented Reality Virtual Try-On (AR VTO) so consumers can try cosmetics virtually before buying them. This study aims to analyze the effect of AR VTO technology on consumer purchasing decisions on Shopee, with reference to the Technology Acceptance Model (TAM). This study uses a quantitative method by distributing questionnaires to 124 respondents through purposive sampling. Data analysis was performed using frequency distribution and Partial Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. The results show that consumers consider the AR VTO feature to be useful (perceived usefulness) and easy to use (perceived ease of use). Both variables have a positive influence on purchase interest, which in turn affects the purchase decision of cosmetics on Shopee. These findings show that the use of AR VTO technology in cosmetic products can help consumers in online shopping, especially in choosing colors according to individual preferences.